2021
DOI: 10.3390/biology10100982
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Beneficial Alleles from Plant Genetic Resources into the Wheat Germplasm

Abstract: Wheat (Triticum sp.) is one of the world’s most important crops, and constantly increasing its productivity is crucial to the livelihoods of millions of people. However, more than a century of intensive breeding and selection processes have eroded genetic diversity in the elite genepool, making new genetic gains difficult. Therefore, the need to introduce novel genetic diversity into modern wheat has become increasingly important. This review provides an overview of the plant genetic resources (PGR) available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 255 publications
(299 reference statements)
1
57
0
1
Order By: Relevance
“…Moreover, the initial process of domestication might have taken approximately 2–3,000 years ( Kislev, 1984 ; Tanno and Willcox, 2006 ) as seen from the archeological records where fragile, partly fragile, and nonfragile spikes can be found in the same farming sites, providing high chances to hybridize. Consistent with these biological and archeological data, the variation in the domesticated-emmer genome includes ∼73% of that of wild emmer ( Zhou et al, 2020 ; Keilwagen et al, 2022 ; Sharma et al, 2021 ). Genotyping of T. aestivum landraces has shown that a significant part of the variation in wild or domesticated tetraploid wheat has also found its way into the A and B subgenomes of the bread wheat genome suggesting that there was only a limited genetic barrier between tetraploid and hexaploid wheat ( Dvorak et al, 2006 ).…”
Section: Evolution Under Allopolyploidysupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, the initial process of domestication might have taken approximately 2–3,000 years ( Kislev, 1984 ; Tanno and Willcox, 2006 ) as seen from the archeological records where fragile, partly fragile, and nonfragile spikes can be found in the same farming sites, providing high chances to hybridize. Consistent with these biological and archeological data, the variation in the domesticated-emmer genome includes ∼73% of that of wild emmer ( Zhou et al, 2020 ; Keilwagen et al, 2022 ; Sharma et al, 2021 ). Genotyping of T. aestivum landraces has shown that a significant part of the variation in wild or domesticated tetraploid wheat has also found its way into the A and B subgenomes of the bread wheat genome suggesting that there was only a limited genetic barrier between tetraploid and hexaploid wheat ( Dvorak et al, 2006 ).…”
Section: Evolution Under Allopolyploidysupporting
confidence: 70%
“…aestivum , which is of global importance, the other subspecies being only locally cultivated, and we refer to it as bread wheat. In this review, we follow Mac Key’s classification, yet additional classifications were proposed as summarized by Sharma et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…Publicly available data were downloaded from 65 https://doi.org/10.5447/IPK/2019/18 . Additional genomic data was downloaded from EMBL ENA with the following IDs: ERR2936519 and ERR2936122 (GBS data of cv.…”
mentioning
confidence: 99%
“…Sometimes the published information is incorrect or misleading. In this study, we consider the taxon names used by Sharma et al 65 . However, we cannot change existing database entries.…”
mentioning
confidence: 99%
See 1 more Smart Citation